Students’ Reflections on The Use of Electronic Media in Their Writing Class - Istiqlaliah Nurul Hidayati; Abdul Rosyid (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
Writing is one of five skills in English subject, and it is also one of the communication tools in which students express their ideas, thoughts, and feelings. Unfortunately, writing is considered a difficult skill to master. That is why a tool is needed to be used in the teaching of writing. An electronic tool is one of the tools that can support the teacher in delivering the materials in a writing class. Among many electronic tools, PowToon is one of the tools that is suitable for teaching the skill. The web-based software presents the materials with animation features, such as cartoons and transition effects. This research is aimed at investigating the advantages and disadvantages of using PowToon in teaching descriptive text. The respondents were 10 students of a senior high school. The researcher used qualitative research with a narrative inquiry design. Documentation (reflective journal), questionnaires, and interviews were used as instruments for collecting the data. Based on the data collected, it can be seen that the advantages of PowToon as an electronic teaching tool made the learning process interesting, happy, fun, motivating, and understandable. However, the researcher found some disadvantages of this tool as the unclear sound produced by the tool. They could barely hear what the speaker was saying. In addition, the duration of the video was too short, so it made the speech fast and not catchable by the students. Keywords: Descriptive Text, Narrative Inquiry, PowToon, Writing Skill